2018
DOI: 10.1038/s41386-018-0157-y
|View full text |Cite
|
Sign up to set email alerts
|

Methylation in OTX2 and related genes, maltreatment, and depression in children

Abstract: Through unbiased transcriptomics and multiple molecular tools, transient downregulation of the Orthodenticle homeobox 2 (OTX2) gene was recently causatively associated with the development of depressive-like behaviors in a mouse model of early life stress. The analyses presented in this manuscript test the translational applicability of these findings by examining peripheral markers of methylation of OTX2 and OTX2-regulated genes in relation to measures of depression and resting-state functional connectivity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 33 publications
(39 reference statements)
1
26
0
Order By: Relevance
“…More recently, the Illumina 450K BeadChip array was used by the same group in another study of ELA and MDD that sought to predict differential DNA methylation in maltreated children. In this study (Kaufman et al, 2018), methylation of the Orthodenticle homeobox 2 ( OTX2 ) gene significantly predicted depression in saliva samples of maltreated children compared to controls (Table 1) (Kaufman et al, 2018).…”
Section: Genome-wide and Multiple Loci Studiesmentioning
confidence: 73%
See 1 more Smart Citation
“…More recently, the Illumina 450K BeadChip array was used by the same group in another study of ELA and MDD that sought to predict differential DNA methylation in maltreated children. In this study (Kaufman et al, 2018), methylation of the Orthodenticle homeobox 2 ( OTX2 ) gene significantly predicted depression in saliva samples of maltreated children compared to controls (Table 1) (Kaufman et al, 2018).…”
Section: Genome-wide and Multiple Loci Studiesmentioning
confidence: 73%
“…Imaging data revealed that methylation of OTX2 is associated with increased functional connectivity between the ventromedial prefrontal cortex and structures of the medial frontal cortex that have been implicated in MDD- such as the paracingulate gyrus, frontal pole, and subcallosal gyrus (Table 1) (Kaufman et al, 2018).…”
Section: Genome-wide and Multiple Loci Studiesmentioning
confidence: 99%
“…Focusing on response to antidepressant treatment, we could identify response-associated transcript profiles in peripheral blood samples of mice, predicting antidepressant treatment response with an accuracy of almost 80% in a patient population ( 26 ). Those and other ( 39 , 40 ) examples of translational studies are encouraging. Importantly, for any translational approach in psychiatry, the research questions originating from the daily clinical situation (i.e., Why does one patient respond to the antidepressant, whereas another does not?…”
Section: A Plea For Careful Translational and Transdiagnostic Researcmentioning
confidence: 79%
“…Its transient knockdown in the VTA increased stress susceptibility, and its overexpression was associated with reverse effects [ 44 ]. The role for the OTX2 gene was confirmed in the study of stress-related depressive disorder pathophysiology in children [ 45 ]. Otx2 is involved in the regulation of the number of VTA neurons with efficient dopamine uptake [ 46 ] and is considered one of the genes with a key role in midbrain dopaminergic neuron development and the regulation of their survival and physiology [ 47 ].…”
Section: Discussionmentioning
confidence: 99%